2000
DOI: 10.1097/00004647-200008000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Altered Central Nervous System Cytokine-Growth Factor Expression Profiles and Angiogenesis in Metallothionein-I+II Deficient Mice

Abstract: Summary:To study the importance of metallothionein-I and -II (MT-I+II) for brain inflammation and regeneration, the authors examined normal and MT-I+II knock-out (MT-KO) mice subjected to a cortical freeze injury. Normal mice showed profound neurodegeneration, inflammation, and gliosis around the injury, which was repaired by 20 days postlesion (dpl). However, in MT-KO mice the lesion-associated inflammation was still present as late as 90 dpl. Scanning electron microscopy demonstrated that the number of capil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
1
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 55 publications
11
95
1
1
Order By: Relevance
“…Our finding in the present study indicates MT plays an important role in VEGF expression in the heart under diabetic conditions through restoration of HIF-1α transcriptional activity. This finding is in an agreement with a previous observation that MT plays a major regulatory role in the angiogenesis process [15].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our finding in the present study indicates MT plays an important role in VEGF expression in the heart under diabetic conditions through restoration of HIF-1α transcriptional activity. This finding is in an agreement with a previous observation that MT plays a major regulatory role in the angiogenesis process [15].…”
Section: Discussionsupporting
confidence: 94%
“…MT also plays important roles in other biological functions, such as anti-oxidation. Some studies have shown that the absence of MT results in a reduction of the expression of several angiogenic factors in mice, such as vascular endothelial growth factor (VEGF) [15]. Down-regulation of VEGF in the heart is associated with the increased risk of cardiovascular morbidity and mortality in patients with diabetes [16].…”
Section: Introductionmentioning
confidence: 99%
“…(MTOEC) in our findings is clearly different because (a) it is highly and specifically restricted to the subpial area of the spinal cord, at the same location of putative target cell in the ENU carcinogenesis model 6 and (b) the staining pattern of the affected cells is far more intense, affecting both cytoplasm and nucleus, than the eventual findings in positive cells of control animals or in the inflammatory stimulated MT expression, as reported in the literature 10 . The MTOEC herein described are similar to the previously described MTOEC that spread in the colon and liver of mouse treated with a single dose of carcinogen 5,11 .…”
Section: Figure 1 Spinal Cord Of Rat Immunostained For Metallothioneicontrasting
confidence: 93%
“…It is known that MT is involved in the regulation of the functions of endothelial cells, as well as in their protection against cytotoxic agents 18 . MT knock-out (MT-KO) mice presented dramatically decreased IL-6-induced angiogenesis caused by cortical freeze injury, suggesting that the MT have major regulatory functions in the angiogenesis process 10 . Interestingly, recent data suggest that stem cells of glioblastoma are situated in close proximity to endothelial cells and seem to be dependent on cues from aberrant vascular niches that mimic the normal neural stem cell niche, facilitating communication between these cell types, what may influence the stem cell regulation 19,20 .…”
Section: Figure 1 Spinal Cord Of Rat Immunostained For Metallothioneimentioning
confidence: 99%
“…In accordance, the opposite was observed in MT-1&2-null mice (98), pointing to an essential role of MT-1&2 in coping with ischemic damage of the brain. Other studies with transgenic mice have equally involved MT-1&2 as important proteins following damage elicited by kainic acid-induced seizures (94), gliotoxins (105, 122), 6-hydroxydopamine (123), amyotrophic lateral sclerosis (38, 100), multiple sclerosis (103,124), traumatic brain injury (28,125,126), and transgenic IL-6-induced neuropathology (127)(128)(129). All of the above are presumably quite different models of brain injury, yet the general impression is that MT-1&2 have similar effects in all cases, namely, decreasing oxidative stress, inflammation and apoptosis in the CNS.…”
Section: Transgenic Mice Show That Metallothionein-1and2 Are Essential mentioning
confidence: 99%